Use of additive manufacturing on models for sand casting process - Martin-Bejar, Sergio; Bermudo-Gamboa, Carolina; Trujillo-Vilches, Francisco Javier; Sevilla-Hurtado, Lorenzo (Universidad Politécnica de Cartagena, 2018)
Casting is a forming process based on material pouring in liquid state. Heat is applied to melt the material from its solid state and pour it in a mold previously constructed to obtain the desired shape after letting it cool. Molds can be permanent or expendable. In sand casting processes, the mold is manufactured from a model that usually is extracted before pouring the melted material (Figure 1). To obtain the part, the sand model needs to be destroyed. Notwithstanding, the sand can be reused several times for new molds. Several elements are needed to obtain a part by a sand casting process: permanent patterns, flasks (cope and drag), gating system (pouring cup, sprue, risers and feeding channels) and cores (only if it is needed). The aim of this work is the manufacturing of some of these elements by additive manufacturing process. The equipment will be used for the practical activities (Figure 1) that currently take place on the subjects where this topic is taught, in the different Degrees in Industrial Engineering at the University of Malaga.
Keywords: Ingeniería industrial - Congresos; Additive manufacturing; Sand casting; Permanent model; Expendable mold